PERAN SEA CHEST DALAM OPERASIONAL KAPAL - Salim Salim (Sekolah Tinggi Maritim Yogyakarta, 2017)
The sea water on board a ship is very required. Sea water isneeded continuously both during the engine operation and vesseloperation. Sea water system is used as a cooling system, ballast, firefighting treatment and so on. The sea water is conveyed on boardthrough the scupper at the bottom part of the water line near the engineroom which is called sea chest. There are minimumly two scuppers.One of it is laid in the upper side and functions in the shallow waterand the other one is located rather down and it is used in a deep water.Sea chest consists of some components to supply the need of sea waterefficiently. Besides, sea chest has to be effectively functioned thoughthe vessel is in listing situation around 22,5 degree.Keywords: sea chest, function, location and equipment